Associations between consumption of coffee and caffeinated soft drinks and late stillbirth—Findings from the Midland and North of England stillbirth case-control study. (January 2021) - Heazell, Alexander E.P.; Timms, Kate; Scott, Rebecca E.; Rockliffe, Lauren; Budd, Jayne; Li, Minglan; Cronin, Robin; McCowan, Lesley M.E.; Mitchell, Edwin A.; Stacey, Tomasina; Roberts, Devender; Thompson, John M.D.
Abstract: Objective: The consumption of caffeinated drinks and soft drinks is widespread in society, including by pregnant women. Data regarding the association of caffeine intake and stillbirth are varied. We aimed to investigate the degree of consumption of caffeinated drinks or soft drinks in the last four weeks of pregnancy in women who experienced a late stillbirth compared to women with ongoing live pregnancies at similar gestation. Influences on maternal caffeine intake and soft drink consumption during pregnancy were also investigated. Study Design: A case-control study undertaken in 41 maternity units in the United Kingdom. Cases were women who had a singleton non-anomalous stillbirth ≥28 weeks' gestation (n = 290) and controls were women with an ongoing pregnancy at the time of interview (n = 729). Data were collected using an interviewer-administered questionnaire which included questions regarding consumption of a variety of caffeinated drinks and soft drinks in the last four weeks of pregnancy as well as other behaviours (e.g. cigarette smoking). Results: Multivariable analysis adjusting for co-existing demographic and behavioural factors found the consumption of instant coffee, energy drinks and cola were associated with increased risk of stillbirth. There was an independent association between caffeine intake and late stillbirth (adjusted Odds Ratio 1.27, 95 % Confidence Interval (95 %CI) 1.14, 1.43 for each 100 mg increment/day). 15 % of cases and 8% of controls consumed more than the World Health Organisation (WHO) recommendation (>300 mg of caffeine/day; aOR 2.30, 95 % CI 1.40, 4.24). The population attributable risk for stillbirth associated with >300 mg of caffeine/day was 7.4 %. The majority of respondents reduced caffeine consumption in pregnancy. Midwives and internet resources were the most frequently used sources of information which influenced maternal behaviour with regard to soft drinks and caffeine, and this did not differ between cases and controls. Conclusions: Women should be informed that consumption of caffeine during pregnancy is associated with increased risk of stillbirth, particularly at levels greater than recommended by the WHO (>300 mg/day). Recommendations from midwives and internet-based resources are likely to be the most effective means to influence maternal behaviour.